The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1021/jacs.3c08770
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Functionality of Self-Assembled 2D Platelets in the Third Dimension

Tianlai Xia,
Zaizai Tong,
Yujie Xie
et al.

Abstract: The decoration of 2D nanostructures using heteroepitaxial growth is of great importance to achieve functional assemblies employed in biomedical, electrical, and mechanical applications. Although the functionalization of polymers before self-assembly has been investigated, the exploration of direct surface modification in the third dimension from 2D nanostructures has, to date, been unexplored. Here, we used living crystallization-driven self-assembly to fabricate poly(ε-caprolactone)-based 2D platelets with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 60 publications
(92 reference statements)
0
0
0
Order By: Relevance
“…The precise bottom-up solution self-assembly is a powerful tool for customizing and tuning functional nanocomposite materials. [11][12][13][14][15][16][17][18] These uniform polymeric nanostructures are able to replace inhomogeneous polymer additives made using top-down methods, allowing the exploration of the structure-function relationship of nanocomposites, which facilitates the preparation of gels with controllable properties. [11] Several studies have shown the forceful ability of nanoparticles formed by the bottom-up assembly to improve the mechanical properties of nanocomposites for adhesive, tissue simulation, and antibacterial applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The precise bottom-up solution self-assembly is a powerful tool for customizing and tuning functional nanocomposite materials. [11][12][13][14][15][16][17][18] These uniform polymeric nanostructures are able to replace inhomogeneous polymer additives made using top-down methods, allowing the exploration of the structure-function relationship of nanocomposites, which facilitates the preparation of gels with controllable properties. [11] Several studies have shown the forceful ability of nanoparticles formed by the bottom-up assembly to improve the mechanical properties of nanocomposites for adhesive, tissue simulation, and antibacterial applications.…”
Section: Introductionmentioning
confidence: 99%
“…Both the Dove and the O'Reilly groups have made many contributions to the performance regulation of nanocomposites using uniform nanostructures prepared by bottom-up self-assembly. [13,15,16,19,20,28] Poly(ɛcaprolactone)-based 1D cylindrical micelles as nanofillers of mimicking collagen morphology physically or ionically interacted with natural polymeric hydrogel networks to enhance the mechanical properties of nanocomposites. [19,20] The cationic 1D cylinders showed higher reinforcement in the mechanical properties of alginate-based hydrogels compared to their cationic 0D spheres and 1D neutral cylinders.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the “living” CDSA strategy, analogous to living chain-growth polymerization, promotes epitaxial growth of solubilized polymer (unimer) from the preformed crystalline seeds, enabling precise size control of the final nanostructures according to the unimer-to-seed ratio (U/S ratio). As a result, synthesis of 1D nanofibers and 2D nanostructures including triangles, rectangles, hexagons, , and diamonds ,,, has been successful. However, the limitation of 2D CDSA, to date, is that the independent control of each width and length has not been achieved as the 2D nanosheets grow in both directions simultaneously. , Considering that the charge mobility of semiconducting materials varies along different crystal plane directions, realizing independent dimension control over the specific direction of the crystal would be highly beneficial for the electronic applications of 2D nanomaterials. ,,, …”
Section: Introductionmentioning
confidence: 99%